Studi Aplikasi Hadis Era Mobile - Rahmad Tri Hadi (Islam Transformatif : Journal of Islamic Studies, 2020)
Hadith studies have experienced very rapid development. This is because many developing various applications or software that can facilitate the study of Hadith. The application and software are then not only a tool in the research activities of Hadith, but also for the benefit of studying the Hadith by the general public. Thus, the application or software must be developed so that it can be sought after and used by the general public. One such application is "One Day One Hadith" developed by the Hadith Study Center in mobile form. This mobile application is based on Android so that it can be used easily in all places and times. This application contains the interesting simple Hadiths from the Shahih Bukhari and is presented in different themes. The pattern of presentation is very interesting because every day a notification will be sent giving an overview of the Hadith of the day. With descriptive-analytical methods, this paper will examine the application 'Go to Heaven', starting from thea brief history of hadith literacy and the history of the hadith of the mobile era (digital), background of its development, features, patterns of presentation of the Hadith and their advantages and disadvantages.